2019
DOI: 10.3390/nu11061324
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Sleep Quality in Southern Italian Adults

Abstract: Background: Current evidence supports the central role of a subclinical, low-grade inflammation in a number of chronic illnesses and mental disorders; however, studies on sleep quality are scarce. The aim of this study was to test the association between the inflammatory potential of the diet and sleep quality in a cohort of Italian adults. Methods: A cross-sectional analysis of baseline data of the Mediterranean healthy Eating, Aging, and Lifestyle (MEAL) study was conducted on 1936 individuals recruited in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 58 publications
(64 reference statements)
1
42
0
Order By: Relevance
“…However, these restaurants may also offer nutrient balanced foods, which are quickly prepared and eaten during a short time. Other research has demonstrated that high calorie, low-nutrient density foods with high proinflammatory potential are those foods associated with sleep problems, rather than the fast food regardless its nutritional value [ 44 , 45 ]. Assessment of carbonated soft drinks did not specify energy drinks which are also known to be associated with reduced sleep quality [46] .…”
Section: Discussionmentioning
confidence: 99%
“…However, these restaurants may also offer nutrient balanced foods, which are quickly prepared and eaten during a short time. Other research has demonstrated that high calorie, low-nutrient density foods with high proinflammatory potential are those foods associated with sleep problems, rather than the fast food regardless its nutritional value [ 44 , 45 ]. Assessment of carbonated soft drinks did not specify energy drinks which are also known to be associated with reduced sleep quality [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary (poly)phenols have been related to several potential health benefits [20]: recently, they have been hypothesized to also play a role in brain health [21,22]. We previously reported that individuals more adherent to healthy dietary patterns (i.e., the Mediterranean diet) and to a diet with low inflammatory potential were more likely to have higher sleep quality [23,24]. In the present study, we aimed to test whether total, subclasses of and individual (poly)phenols may be candidate molecules associated with sleep quality in a cohort of Italian adults.…”
Section: Introductionmentioning
confidence: 99%
“…35 Another study found that following a diet with low inflammatory index (such as DASH diet) improved sleep quality. 36 Dietary modification may be a practical approach to preventing sleep disorders. In line with our results, in a previous study, it has been found that a sodium-restricted diet (maximum intake of 3 g of sodium per day) for one week improved the symptoms of obstructive sleep apnea compared with control group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DASH diet has been associated with inflammation, 43 which in turn is associated with scarce sleep medicine, 44 Up to date, only one study investigated the correlation between inflammatory potential of the diet and sleep, and showed that individuals adherent to a proinflammatory diet report worse sleep quality. 36 Studies have shown that weight disorders such as overweight and obesity are usually associated with sleep problems, 45 and some studies have shown that adherence to DASH diet has helped to correct this trend; 46,47 therefore, it is expected that adherence to DASH diet can improve some sleep disorders such as insomnia. Interestingly, obesity has been demonstrated to be a modifying factor of the correlation between higher adherences to the Mediterranean diet and sleep features.…”
Section: Discussionmentioning
confidence: 99%